Adaptations to the participatory learning and action cycle in resource-limited settings: an observational study. (November 2017) - Martin, Jennifer S; Fottrell, Edward; Black, Georgia; Vindrola, Cecilia; Lakhanpaul, Monica
Abstract: Background: New approaches are needed to engage UK minority populations, who are disproportionately affected by non-communicable diseases. Community mobilisation through women's groups using the participatory learning and action (PLA) cycle has successfully reduced the prevalence of adverse maternal and neonatal health outcomes in Bangladesh, India, Nepal, and Malawi. The PLA cycle offers a method of health promotion by guiding participants through a four-stage cycle of identifying and prioritising population issues, designing strategies to combat issues, and evaluating the strategies post implementation. The aim of this study was to further understand how to adapt the PLA cycle for nutrition-related ill health in the Bangladeshi population of Tower Hamlets, East London. Methods: One-on-one semi-structured key informant interviews with professionals who advised or delivered the model across seven trials of adapting the PLA cycle for nutrition-related ill health were conducted. Gaps in the published literature from 12 papers informed questions for the topic guide around processes of adaptation. Thematic analysis and framework analysis were applied to reduce and order the data. Findings: 14 interviews generated themes that highlighted the benefits of using a local non-governmental organisation to facilitate communication with the target population. Each trial had a formative research stage that explored adaptation based on ethical principles and cultural differences. Adaptation was informed by a pilot and then rapid feedback response. The data demonstrated that domains of geographical context such as environmental morphology (rural or urban) could influence adaptation. Interpretation: The data shows that using a local non-governmental organisation is a pragmatic method of embedding the trial in the target population. Themes emerged indicating that it may be unethical to implement an intervention without exploring social nuances and cultural norms in context. Adaptation can encourage acceptability of an intervention, optimise feasibility, and increase appropriateness. Whereas some adaptations were evidence based, some were practical, indicating that a logical and consistent adaptation process could optimise transferability of the original model in the future. Adaptation for culture and context could support embedding the intervention within the Bangladeshi population in Tower Hamlets. Funding: National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care North Thames.